Selected contribution: High-altitude natives living at sea level acclimatize to high altitude like sea-level natives. - Rivera-Ch, M; Gamboa, A; Léon-Velarde, F; Palacios, J; O'Connor, D; Robbins, P (2003)
Sea-level (SL) natives acclimatizing to high altitude (HA) increase their acute ventilatory response to hypoxia (AHVR), but HA natives have values for AHVR below those for SL natives at SL (blunting). HA natives who live at SL retain some blunting of AHVR and have more marked blunting to sustained (20-min) hypoxia. This study addressed the question of what happens when HA natives resident at SL return to HA: do they acclimatize like SL natives or revert to the characteristics of HA natives? Fifteen HA natives resident at SL were studied, together with 15 SL natives as controls. Air-breathing end-tidal Pco(2) and AHVR were determined at SL. Subjects were then transported to 4,300 m, where these measurements were repeated on each of the following 5 days. There were no significant differences in the magnitude or time course of the changes in end-tidal Pco(2) and AHVR between the two groups. We conclude that HA natives normally resident at SL undergo ventilatory acclimatization to HA in the same manner as SL natives.